Periphery and Small Ones Matter Interplay of Policy and Social Capital - Azis, Iwan J. (Springer Nature Singapore : Imprint: Springer, 2022)
This open access book analyzes the dualism and inequality insofar as how it is manifested in interregional disparity and small enterprises. Using the case of Indonesia, the author considers how the general direction of policy should be to mitigate the effects of agglomeration forces leading towards concentration, and exploit the same forces by encouraging small businesses to operate in a cluster for collective action. The book addresses these issues by focusing on the role of interactions between policies and institutions, of which social capital is an important part. "Iwan Azis' new book has all the elegance of his deep understanding of institutions and policies......(it) has widespread interest for those working on problems of the populous countries of the Third World." -Yoginder. K. Alagh, Former Minister of Power, Planning & Science & Technology of India "Given that inequality is expected to rise with the pandemic, this is a timely publication." -Mari E Pangestu, Managing Director of Development Policy and Partnerships, World Bank "The value of the book lies in the fact that the recommendations about policy are based on real cases." -Taeho Bark, Former Trade Minister of Korea "This path-breaking book by one of Indonesia's most experienced economists focuses on how MSMEs can drive development and reduce both forms of inequality......Essential reading." -Howard Dick, University of Melbourne "Just listen to them. This is the striking conclusion of this excellent study of the interface between policy and social capital in nurturing MSMEs." -Ravi Kanbur, Cornell University Iwan J Azis is Professor at Cornell University and University of Indonesia. His research focuses on the interlink between macro-financial economics, social-institutional issues, and spatial inequalities in emerging markets. This book is written during his role as a research scholar in BI Institute.